Problematika Kelembagaan Partai Politik : Studi Terhadap Fungsi Representasi Partai Politik Pascareformasi - Novi Winarti; Nazaki Nazaki (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2019)
Political parties have functions representation, conversion and aggregation, integration, persuasion, repression, recruitment and selection of leaders, considerations and formulation of policies and control of the government. However, after the reform which was marked by the opening of the widest possible tap of democracy, it did not make all the functions of the political party work. Even today, the number of public dissatisfaction with the performance of political parties is still very high. So the thing that is interesting is why political parties in the reformation period experienced a crisis of representation functions. This study was conducted using qualitative desktiptif analysis methods through literature review. The study found that the crisis of representation functions experienced by political parties during the reform period was caused by the weakness of the political party institutions themselves, including the systemic aspects which caused weak formal representation, low values ​​/ ideology of political parties which caused weak symbolic representation and low authority what political parties have in making decisions leads to low political party substantive representation.